Diskriminasi Ras Dan Etnis Dalam Prespektif Hadits Dan Pasal 244 KUHP - AzZahra, Naila Syafa; Arifin, Tajul (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Article 244 of the latest Indonesian Criminal Code (KUHP) prohibits racial and ethnic discrimination. However, its implementation is still subject to debate. This research aims to analyze the hadith perspective on Article 244 of the new Criminal Code regarding racial and ethnic discrimination. This research uses qualitative methods with a text analysis approach. Information is collected from hadith books and other related literature. Information is analyzed using deductive and inductive methods. The research results show that the hadith has a perspective that is in line with Article 244 of the new Criminal Code regarding racial and ethnic discrimination. These hadiths teach that all humans are equal before Allah SWT, and there should be no discrimination based on race or ethnicity. This research recommends that the new interpretation of Article 244 of the Criminal Code considers the hadith perspective. This is important to ensure that the application of this article does not violate the principles of justice and equality.